2013
DOI: 10.1038/cddis.2013.52
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenin 3+ cells contribute to β-cell neogenesis and proliferation in injured adult mouse pancreas

Abstract: We previously showed that injury by partial duct ligation (PDL) in adult mouse pancreas activates Neurogenin 3 (Ngn3)+ progenitor cells that can differentiate to β cells ex vivo. Here we evaluate the role of Ngn3+ cells in β cell expansion in situ. PDL not only induced doubling of the β cell volume but also increased the total number of islets. β cells proliferated without extended delay (the so-called ‘refractory' period), their proliferation potential was highest in small islets, and 86% of the β cell expans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
94
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 27 publications
4
94
0
1
Order By: Relevance
“…In contrast, we concluded that neogenesis was insignificant in PDL pancreases because Ngn3 transcript levels were below 0.2-fold of the normalized level seen in the duodenal tissue (6). The hypothesis that the number of Ngn3 + transitional intermediate cells or the individual Ngn3 level per cell is rate-limiting for b-cell neogenesis should be testable.…”
Section: Ngn3 Transcript Level and B-cell Neogenesismentioning
confidence: 85%
See 4 more Smart Citations
“…In contrast, we concluded that neogenesis was insignificant in PDL pancreases because Ngn3 transcript levels were below 0.2-fold of the normalized level seen in the duodenal tissue (6). The hypothesis that the number of Ngn3 + transitional intermediate cells or the individual Ngn3 level per cell is rate-limiting for b-cell neogenesis should be testable.…”
Section: Ngn3 Transcript Level and B-cell Neogenesismentioning
confidence: 85%
“…We found that the global Ngn3 mRNA level detected by quantitative RT-PCR in the PDL tail showed a strong correlation with 1) number of b-cells derived from Ngn3 + cells; 2) number of islets that showed dilution of prelabeled b-cells by unlabeled b-cells at 14 days post-PDL, particularly small ones containing 20 or fewer b-cells; and 3) the overall dilution of prelabeled b-cells scored at 35 days post-PDL (6). Together, these data support the idea that precursors of at least some new b-cells derived under PDL context are from a non-b-cell source(s).…”
Section: Ngn3 Transcript Level and B-cell Neogenesismentioning
confidence: 94%
See 3 more Smart Citations